2016
DOI: 10.1186/s12918-016-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of essential proteins in Corynebacterium pseudotuberculosis based on protein-protein interaction networks

Abstract: Background Corynebacterium pseudotuberculosis (Cp) is a gram-positive bacterium that is classified into equi and ovis serovars. The serovar ovis is the etiological agent of caseous lymphadenitis, a chronic infection affecting sheep and goats, causing economic losses due to carcass condemnation and decreased production of meat, wool, and milk. Current diagnosis or treatment protocols are not fully effective and, thus, require further research of Cp pathogenesis.ResultsHere, we mapped known protein-protein inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Some members of this family (nusG) has already been reported as drug target. Furthermore, rpsH and smpB are also reported as potential drug target by Folador et al, 2016 in their in silico study [ 41 ]. Protein DIP1084 is Putative iron transport membrane protein (FecCD-family) and DIP0983 is uncharacterized Hypothetical Protein that need to be characterized experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Some members of this family (nusG) has already been reported as drug target. Furthermore, rpsH and smpB are also reported as potential drug target by Folador et al, 2016 in their in silico study [ 41 ]. Protein DIP1084 is Putative iron transport membrane protein (FecCD-family) and DIP0983 is uncharacterized Hypothetical Protein that need to be characterized experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…The interolog mapping approach was used to translate the identified interactions to V. parahaemolyticus MSR16 and MSR17 strains, which implies that when two proteins interact, their orthologous partners would also interact. 59 - 61 STRING, as described in eggNOG, exploits hierarchically organized orthologous group relations to retrieve association between relevant species. 62 - 64 …”
Section: Methodsmentioning
confidence: 99%
“…Using interolog mapping, 12 putative drug targets were identified in methicillin-resistant Staphylococcus aureus , including a histone deacetylase ( 241 ). A predicted Corynebacterium pseudotuberculosis interactome was used to identify 41 essential proteins as candidates for infection diagnosis in livestock, highlighting the tryptophan biosynthesis pathway as a potential drug target ( 200 ). The network also revealed that this species may use multiple iron acquisition strategies in low iron environments.…”
Section: Drug Targetsmentioning
confidence: 99%